Cerebral small vessel disease combined with cerebral collaterals to predict the prognosis of patients with acute large artery atherosclerotic stroke - Wei, Cunsheng; Shen, Tingwen; Tang, Xuelian; Gao, Yuanyuan; Yu, Xiaorong; Chen, Xuemei (Frontiers in Neurology, 2022)
Background and purpose Besides cerebral collaterals, few studies have examined other additional factors affecting the prognosis of patients with large artery atherosclerotic (LAA) stroke. Our study aims to explore the effect of the cerebral small vessel disease (SVD) and the effects of its interaction with cerebral collaterals on the prognosis of patients with acute LAA stroke. Method Patients aged 18 years or older with LAA stroke within 24 h after stroke onset were consecutively enrolled. The functional outcome was determined using the modified Rankin Scale (mRS) at 3 months after stroke onset. Logistic multivariate analyses were used to identify the risk factors for stroke prognosis. Receiver operating characteristic (ROC) curves were constructed to compare the effects of cerebral collaterals and SVD on predicting the prognosis. Results Of the 274 enrolled patients, 174 (63.50%) were identified as having a favorable prognosis, and 100 (36.50%) were identified as having an unfavorable prognosis. After adjusting for covariates, the logistic regression analysis identified that unfavorable prognosis was related to the total SVD score (Model 1, adjusted odds ratio = 1.73, 95% CI: 1.15–2.61, P < 0.01; Model 2, adjusted odds ratio = 1.85, 95% CI: 1.23–2.79, P < 0.01) and Tan score (Model 1, adjusted odds ratio = 0.38, 95% CI: 0.23–0.64, P < 0.01; Model 2, adjusted odds ratio = 0.52, 95% CI: 0.33–0.82, P < 0.01). Compared with cerebral collaterals (AUC = 0.59; 95% CI: 0.52–0.67; P < 0.01) or SVD (AUC = 0.62; 95% CI: 0.56–0.69; P < 0.01) alone, the combination of collaterals and SVD (AUC = 0.66; 95% CI: 0.59–0.73; P < 0.01) had higher diagnostic value for an unfavorable prognosis, and the optimal sensitivity and specificity were 77.01 and 53.00%, respectively. Conclusions The total SVD burden was related to the prognosis of patients with LAA stroke. Compared with cerebral collaterals or SVD alone, cerebral collaterals combined with total SVD burden are better at predicting the prognosis of patients with acute LAA stroke.